Pittura e poesia negli scritti teorici e nella poesia ecfrastica del surrealista Ūrḫān Muyassar - Monaco, Arturo (Annali di Ca’ Foscari: Serie Orientale, 2022)
This contribution aims to explore the relation between painting and poetry in the thought and in the poetic production of the Syrian poet Ūrḫān Muyassar. The first part of the study offers an overview of the relationship between painting and poetry, with particular reference to the reflections both within the Arab-Islamic culture and within the surrealist movement. In the second part, the focus shifts to Muyassar. After a brief introduction on the poet, the analysis first takes into consideration his theoretical contribution on the relationship between painting and poetry, then the poetic one, through three examples of ekphrastic poems.